Analysis of Sustainable Tourism Industry Development through the Role of Transportation Infrastructure and Government Regulation - Taali, Muhammad; Susanto, Fredy; Wibowo, Sundaru Guntur; Puspitasari, Dyah Ayu Kunthi; Amri, Lala Hucadinota Ainul (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study aims to analyze the development of sustainable tourism with a focus on the role of transportation infrastructure and government regulations as determining factors for the success of coastal tourism destinations in East Java. Using a descriptive qualitative approach, data were obtained through in-depth interviews, field observations, and document studies. The results show that improvements in transportation infrastructure, such as improved road access and port facilities, contribute to increased accessibility and economic opportunities for local communities. However, the limitations of public transportation, the unavailability of environmentally friendly modes, and the uneven distribution of supporting infrastructure are still obstacles. On the other hand, the government has established a tourism management policy, but its implementation has not been optimal due to inconsistent cross-sector coordination and supervision. The study confirms that success in sustainable tourism requires integration between strengthening infrastructure, collaborative governance, and utilizing supporting technologies.